Tramadol’s Inhibitory Effects on Sexual Behavior: Pharmacological Studies in Serotonin Transporter Knockout Rats - Esquivel-Franco, Diana C.; Olivier, Berend; Waldinger, Marcel D.; Gutiérrez-Ospina, Gabriel; Olivier, Jocelien D. A. (Frontiers in Pharmacology, 2018)
Tramadol is an effective pharmacological intervention in human premature ejaculation. To investigate whether the inhibitory action of tramadol is primarily caused by its selective serotonin reuptake inhibitory (SSRI) effects we tested the dose-response effects of tramadol on sexual behaviour in serotonin transporter wildtype (SERT+/+), heterozygous (SERT+/-) and knockout (SERT-/-) rats. To investigate whether other mechanisms contribute to the inhibitory effects, WAY100,635, a 5-HT1A receptor antagonist and naloxone, a μ-opioid receptor antagonist, were tested on sexual behaviour together with tramadol. Tramadol dose-dependently decreases sexual activity in all genotypes. In all studies, SERT+/- rats did not respond differently from SERT+/+ rats. WAY100,635 did not affect sexual activity in SERT+/+, but dose-dependently reduced sexual activity in SERT-/- rats. WAY100,635 (0.3 mg/kg) combined with tramadol (20 mg/kg) significantly reduced sexual activity in SERT+/+ and even stronger in SERT-/- rats. Naloxone did not affect sexual behavior consistently in SERT+/+ rats, while in SERT-/- rats all doses reduced ejaculation frequency mildly. Combining naloxone (20 mg/kg) and tramadol (20 mg/kg) decreased ejaculation frequencies in both genotypes. Interestingly, combining tramadol (20 mg/kg), WAY100,635 (0.3 mg/kg) and naloxone (20 mg/kg) led to complete elimination of all sexual activity in both SERT+/+ and SERT-/- rats. These findings suggest that the inhibitory effects of tramadol on male sexual behavior in SERT+/+ rats is mainly, if not exclusively, due to serotonin transporter inhibition, with an important role for 5-HT1A receptors, although influence of other systems (e.g. noradrenergic) cannot be excluded. As SSRIs exert their sexual inhibition after chronic administration, tramadol may be therapeutically attractive as ‘on demand’ therapy for premature ejaculation.